Step-by-step explanation:
y = ax^n + bx^(n-1) ... + z
(0, 1) tells us that the constant term z = 1.
because x = 0 eliminates all other terms. and as the sum is 1, that means z = 1.
for the other pairs I strongly suspect
(-1, 3) : 2×(-1)² + 1 = 2×1 + 1 = 3
(-2, 9) : 2×(-2)² + 1 = 2×4 + 1 = 9
so, the fitting equation is
y = 2x² + 1
21.W hich value of y makes the following equatoin true?
answer:B
Answer:
5
Step-by-step explanation:
Answer:
Step-by-step explanation:
x/70=0.5/20
x=35/20
x=1.75
Ann will need 1.75 cups of sugar.
Hey there!
<span>There is 32 oz per qt. 2qts=64oz. Divide 64 by 6. </span><span> 6 goes evenly into 64 10 times with a remainder. So the answer is 10 glasses.
</span>
Hope this helps!